A reassessment of external demand's contribution to Malta's economic growth - Aaron George Grech; Noel Rapa (Journal of Economic Structures, 2019)
The role of external demand in determining economic growth has undoubtedly increased as a result of globalisation. However, the conventional approach used to assess the contribution to growth of exports diminishes the positive influence of higher foreign demand by attributing to it the entire increase in a country's import bill. Given that other components of GDP have significant import contents, this approach typically underestimates considerably the importance of external demand in driving growth. This article applies an alternative approach that uses information from input-output tables to apportion imports across all expenditure components, before assessing their relative contribution to GDP growth. When applied to Malta, one of the fastest-growing EU economies, this approach leads to a significant reassessment of external demand's contribution to economic expansion. This is more in line with other macroeconomic indicators, such as the improvement in the country's current account and exports-to-GDP ratio.
Keywords: O47; F43; E32; 330; External trade; Economic growth; Contribution demand categories